Contextual and Individual Variables as Predictors of Energy-Dense Meals in Food Choices - Borbón-Mendívil, Daniela; Tapia-Fonllem, Cesar; Fraijo-Sing, Blanca (Frontiers in Psychology, 2022)
Diets based on meals that provide large amounts of energy and consumed frequently often increase the rate of growth of the body mass index (overweight or obesity) and, in turn, the risk of suffering from non-communicable diseases. In order to make a food choice, it is necessary to search for foods in the environment, taking into account physical and social variables (contextual variables) which, together with individual variables, delimit the situation of food selection. The objective of this study was to evaluate the effect of social facilitation, portion size, salience of food, and food preference or rejection on the selection of energy-dense foods by young college students. To do so, we performed a factorial experiment in which unaccompanied and accompanied participants (levels of social facilitation) as they went through the process of choosing from different options of main dish, beverages, and desserts, then noted the reasons for their selection (preference or rejection of the food). Results showed significant differences between the group of accompanied participants and salience of food in the selection of the energy-dense main dishes and desserts (pizza, spaghetti, and chocolate cake). A significant relationship was also identified between accompanied participants, hedonistic/sensory reasons (food preference or rejection category) and salience of food in the selection of the energy-dense main dish. In conclusion, key findings about the variables that constitute the situation which predicts the selection of energy-dense foods have emerged from this study, when participants and the given level of social facilitation (in this case, being accompanied) where faced with the conditions of the food salience of the meals of their preference regarding its taste and appearance.